Bacterial cellulose production from the litchi extract by Gluconacetobacter xylinus. Issue 1 (2nd January 2016) - Yang, Xiao-Yan; Huang, Chao; Guo, Hai-Jun; Xiong, Lian; Luo, Jun; Wang, Bo; Lin, Xiao-Qing; Chen, Xue-Fang; Chen, Xin-De
ABSTRACT: Although litchi has both nutrient and edible value, the extremely short preservation time limited its further market promotion. To explore processed litchi products with longer preservation time, litchi extract was selected as an alternative feedstock for production of bacterial cellulose (BC). After 2 weeks of static fermentation, 2.53 g/L of the BC membrane was obtained. The trace elements including magnesium (Mg) and sodium (Na) in the litchi extract were partly absorbed in the BC membrane, but no potassium (K) element was detected in it, curiously. Scanning electron microscope (SEM) photographs exhibited an ultrafine network nanostructure for the BC produced in the litchi extract. Analysis of the fourier-transform infrared spectroscopy (FTIR) confirmed the pellicles to be a cellulosic material. Interestingly, X-ray diffraction (XRD) results showed the BC membrane obtained from litchi extract had higher crystallinity of 94.0% than that from HS medium. Overall, the work showed the potential of producing high value-added polymer from litchi resources.